Biblioteki publiczne na Ziemi Lubuskiej w latach 1945-2010 - zarys problematyki = Public libraries in the Lubusz region in the years 1945-2010 ? an outline of the issues - Kotlarek, Dawid (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article outlines the development of public libraries in the Lubusz Voivodeship between 1945 and 2010. It discusses the development of the library network after World War II, changes in the structure of book collections, changes in readership levels, and the staffing situation within libraries. The author highlights the impact of political, administrative, and economic conditions on the functioning of libraries in the region, particularly during the political transformation after 1989. The article concludes by emphasizing the importance of libraries as institutions supporting the development of the information society and their role as spaces for social and cultural activity.
Keywords: biblioteki publiczne; Ziemia Lubuska; historia; czytelnictwo; księgozbiory; sieć biblioteczna; bibliotekarze; województwo lubuskie; rozwój; społeczeństwo informacyjne; public libraries; Lubusz Land; history; reading; book collections; library network; Lubusz Voivodeship; librarians; library development; information society